Quality of Life in Children With Chronic Kidney Disease Using the Hindi Version of PedsQL 3.0 End-stage Renal Disease Module: Perspective of Patient and Caregiver: Quality of Life in Chronic Kidney Disease - Mazahir, Rufaida; Anand, Kanav; Pruthi, Praveen Kumar (Journal of Pediatric Nephrology, 2024)
Background and Aim: Limited data exists on health-related quality of life (HRQOL) in children with chronic kidney disease (CKD) stage 5D and the results often differ. This study assesses the HRQOL in children with CKD stage 5D using the Hindi version of the paediatric quality of life (PedsQL) 3.0 end-stage renal disease module. Methods: This was a cross-sectional, questionnaire-based study conducted between February 2018 and January 2019 at a tertiary-care center in New Delhi, India. HRQOL was assessed in 45 children (age=5-18 years) receiving maintenance dialysis for at least 2 months, using both child self-report and parent-proxy report. Results: Enrolled children had poor HRQOL, with the worst scores observed in the treatmentproblems (TP) domain (child and parent-proxy report). Patients who were on hemodialysis had lower quality of life (QOL) scores compared to subjects on peritoneal dialysis, especially in the TP domain. We found a significant negative impact of adolescent age group (general fatigue [GF], about-my-kidney-disease [AMKD], family and peer interaction [F/PI]), female gender (perceived physical appearance [PPA]), rural residence (total, GF, AMKD), separated parents (AMKD, worry), lower maternal education (GF, communication), higher number of medication intake (AMKD, F/PI), low hemoglobin (communication) and more number of hospitalizations in last six months (F/PI) on HRQOL of enrolled children. Furthermore, the child-reported mean total scores in the domains of GF, TP, F/PI and worry were less favorable compared to parent-reported scores. School attendance was seen in only 15 % of the children. Conclusion: End-stage kidney disease exerts a significant impact on the HRQOL of affected children; therefore, comprehensive management of this disease in children should include QOL assessment.